Development of anti-corrosion coatings using the disposable waste material - Saidi, Norshahirah Mohamad; Shafaamri, Ammar; Wonnie Ma, Iling Aema; Ramesh, Kasi; Vengadaesvaran, Balakrishnan; Ramesh, Subramaniam (Emerald, 2018)
Purpose: The purpose of this study is to develop anti-corrosion coating systems using disposable waste materials. The dissolved polyethylene terephthalate (PET) has been blended with epoxy resin and stoichiometrically cured with a polyamide resin. Design/methodology/approach: Glycolysis process was found to be the most optimum candidate to dissolve PET. The developed coating systems were characterized by Fourier transform infrared spectroscopy for confirmation of the molecular bonding structures. The mechanical properties were characterized by performing pull-off test and cross hatch test for mechanical properties on the coated panel. Also, the glossiness test was used by reflecting light on the coated surface. The corrosion protection performance of the coated mild steel panels was examined using electrochemical impedance spectroscopy. Furthermore, the wettability of the developed coating systems was evaluated by using water contact angle technique. Findings: It was observed that the coating system which contains 10 per cent of dissolved PET (S2) showed the highest adhesion and corrosion protection properties. Originality/value: Recyclable PET bottles have outstanding chemical properties, adhesion properties, low cost, low permeability to gases and solvents making it suitable as a coating with superior barrier properties.